Effects of some physic - chemical characteristics of the soil on earthworms at the Tam Dao national park, Vinh Phuc province - Kim Hoi, Huynh Thi; Tu, Vuong Tan; Tien Trinh, Nguyen Canh (Academia Journal of Biology, 2014)
This paper presents the effects of a number of soil characteristics on earthworms at the Tamdao national park, Vinhphuc province in October 2005. Earthworms and soil samples collected in different biotopes of the natural and anthropogenic lands. The results showed as following: 1 - 38 earthworm species belonging to five genera, four families was found in this area. Among these species, 18 species were found in natural lands and 25 species in anthropogenic lands. Among these genera, Pheretima Kinberg was the dominant genus with the highest species number (34 species). Typically, Pheretima xuongmontis Thai et Samphon was the new record for Vietnam. Among these earthworm species, Pheretima exigua taybacana Thai and Ph. robusta Perrier were the abundant species. 2 - Among soil characteristics, the structure, the acidity and the phosphorus contents have barely relationships with the composition, the density and biomass of earthworm species.